Artificial Intelligence, Identity and Society in Cyberpunk Era in William Gibson’s Novel Neuromancer (International Journal of Scientific Research in Science and Technology, 2024)
William Gibson is a Canadian-American speculative fiction writer known for pioneering the genre of cyberpunk, blending technology, dystopian themes and philosophical exploration. Gibson’s early novels particularly the “Sprawl Trilogy”, Neuromancer, Count Zero, and Mona Lisa overdrive envision a edgy future world where corporations holds immense power hackers navigate virtual realities and advanced tech merges with human experience in dystopian ways. His major themes are fascination with Technology and the Future, Alienation and disconnection, Cynicism and hope, the blurring of Reality and virtuality and a fear of corporate control. His work, Neuromancer is celebrated for introducing concepts like cyberspace and shaping the virtual reality landscape in science fiction creating a vision of internet before it spreads widely. His characters often inhabit the margins of society, dealing with the moral ambiguities of technological progress. He influences us to spans literature, film, and pop culture shaping how we think tech-driven future. This research paper reinterprets the portrayal of technology and societal impacts of a digital, interconnected world.